Pemisahan Spermatozoa Berkromosom X dan Y Kambing Boer dan Aplikasinya Melalui Inseminasi Buatan Untuk Mendapatkan Jenis Kelamin Anak Sesuai Harapan - Dasrul Dasrul; M. Aman Yaman; Zulfan Zulfan (Agricultural Faculty, 2013)
Separation of spermatozoa with x and y chromosome at boer goat and its application by artificial insemination for kid sex purposeABSTRACT. The purposes of this experiment are to investigate the separation of X and Y spermatozoa by measuring the spermatozoa quality, sex ratio between X and Y, capacity of fertility indicated by conception rate and sex ratio of goat boar kids. Samples, used in this experiment, are fresh semen from Boer goat with high quality consists of 4 group treatments with 6 replications 1) group of spermatozoa without separation (control), 2) group of spermatozoa separated by percoll gradient density centrifugation 3 levels (P1), 5 levels (P2) and swine up (P3). The observed parameters are spermatozoa quality, X and Y spermatozoa ratio, fertilitys capacity and sex ratio on the birth. Quality examination of spermatozoa and identify X and Y spermatozoa is based on the standard method of WHO. The conception rate was based on the ratio of pregnant goat after the first insemination. Data of spermatozoa quality and spermatozoa ratio were analyzed by using analisis of variance (ANOVA) and further analysis by LSD if there were differences between treatments. The results of this experiment showed that spermatozoa quality Boer goat significantly reduced (p0,05) after separation with percoll gradient density centrifugation and swim up. Percentage spermatozoa X after percoll gradient density centrifugation was significantly higher (P0,05) compared to control and swim up. Meanwhile, the Y spermatozoa population was significantly higher (P0,05) after swim up treatment compared to percoll gradient density centrifugation and control. The percentage of sex ratio (male: female) after insemination from percoll gradient density centrifugation produced more female than male. On the other hand, insemination from swim up produced more male than female. Sex ratio produced from separation of percoll gradient density centrifugation, swim up was difference from control semen (P0,05). From this experiment, it was concluded that spermatozoa separation by percoll gradient density centrifugation and swim up can be used as one of the methods to separate X and Y spermatozoa and further can be applied to get preferred sex animals.